Meta-Analysis of Inequality Aversion Estimates - Salvatore Nunnari; Massimiliano Pozzi (Center for Economic Studies and ifo Institute (CESifo), 2022)
We conduct an interdisciplinary meta-analysis to aggregate the knowledge from empirical estimates of inequality aversion reported from 1999 to 2022. In particular, we examine 85 estimates of disadvantageous inequality aversion (or envy) and advantageous inequality aversion (or guilt) from 26 articles in economics, psychology, neuroscience and computer science that structurally estimate the Fehr and Schmidt (1999) model of social preferences. Our meta-analysis supports the presence of inequality concerns: the mean envy coefficient is 0:426 with a 95% probability that the true value lies in the interval [0:240; 0:620]; the mean guilt coefficient is 0:290 with a 95% probability that the true value lies in the interval [0:212; 0:366]. Moreover, we observe high levels of heterogeneity, both across studies and across individuals, with estimated parameters sensitive to the experimental task and the subject population.
Keywords: C90; C11; D63; D91; 330; social preferences; inequality aversion; inequity aversion; envy; guilt; meta-analysis; multi-level random-effects model; Bayesian hierarchical model